أخطاء نطق التفخيم والترقيق عند الناطقين بغير العربية: دراسة صوتية حاسوبية - Nurmasturah binti Jamil (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The purpose of this study is to identify the error in pronunciation of Emphasis (Tafkhim) and Non-Emphasis (Tarqiq) Arabic sounds among non-native Arabic undergraduate students at the International Islamic University Malaysia (IIUM). The data from the participants were gathered by recording the participants as they read texts. From the obtained data, the researcher tries to identify the common phonetic errors that are related to Emphasis and Non-Emphasis Arabic sounds. Non-native Arabic students usually face difficulty in pronunciation because the said sounds do not exist in their own mother tongue. There is also serious research attention from experts in the field of study, mainly in practising the Emphasis and Non-Emphasis Arabic sounds in daily conversations. This study was conducted by using inductive and mixed mode methodologies, with the assistance of computer programming. The inductive approach was adopted to collect the sound recordings among the non-native Arabic students from three faculties that specialize in Arabic Language Studies at the International Islamic University Malaysia (IIUM). The participants of this study were nine students. The analytical approach focuses on analysing the obtained results in the view of Emphasis (Tafkhim) and Non-Emphasis (Tarqiq) phonological perspectives. Meanwhile, computer programming was used to record sounds by using two types of computer software; Cool Edit Pro 2.1 and Gold Wave V6. The findings of this study have proven that non-native Arabic students have promising capability in pronouncing Emphasis and Non-Emphasis Arabic sounds except in sad, dad, and za sounds. These findings lend new empirical and theoretical support on the capability of non-native Arabic speakers in improving their phonological skills.